Implementation of Correspondence Guidance for Village Apparatus in Sukajati Village, Haurgeulis District, Indramayu Regency - Dina Nurul Aprilina (Konsultan Jurnal Ilmiah Indonesia, 2025)
Village apparatus is the vanguard of government at the village level who has a strategic role in community development and development. One of the important competencies that must be possessed by village apparatus is the ability in the field of correspondence or correspondence. Through correspondence, village apparatus can convey information, requests, reports, and various other important documents to the government above it, such as sub-districts, regencies/cities, to the central government. The purpose of writing this article is to find out the Implementation of Correspondence Guidance for Village Apparatus in Sukajati Village, Haurgeulis District, Indramayu Regency. The methods used include coaching, socialization, lectures, speakers will deliver material related to concepts, principles, and techniques of good and correct correspondence, then with questions and answers, participants can ask questions and discuss problems they face related to correspondence. To measure the success of its implementation, using pretest and posttest instruments, which then after data processing using the N-Gain Test. Based on the calculation obtained N-Gain percent of 67.56, then the work program that has been implemented is declared quite effective in being applied to seminar participants with village apparatus participants in correspondence coaching activities. These activities include providing pretest and posttest sheets. And to measure the success of this activity, the N-Gain Test and interviews are used, with the results of this activity being quite effective in improving the quality and competence of village apparatus. Therefore, the program implemented has achieved success. Furthermore, the results of this supporting program are expected to be beneficial for village apparatus, and can carry out their duties properly and correctly.